Inventory management and profitability of a company in the automotive sector - Lozano García, Magaly (2021)
The objective of the research was to determine the effect of inventory management on the profitability of the automotive company in the district of Tarapoto, a study that took into account scientific articles oriented and published in EBSCO HOST, redalyc, ProQuest, SciElo, Scopus, Dialnet and SciencieDirect based on the last 5 years. Methodology: It is applied because it relied on theoretical contributions for solution alternatives, with a quantitative approach, descriptive scope, cross-sectional and non-experimental design because no variables were manipulated. As a result of the above mentioned, it was evidenced that at the beginning of the evaluated period the inventory management was deficient, which improved progressively with the application of new policies generating a positive effect on profitability. The research concludes that according to the analysis carried out, the company has the tools to develop the activities correctly, a fact that generates improvement in the management processes and that the implementation of the new policies has had a satisfactory influence on profitability, generating a ROS of 4.75%, ROA of 4.48%, ROE of 37% and ROCE of 112%.